A Biodegradable Hemostatic Gelatin/Polycaprolactone Composite for Surgical Hemostasis. (March 2017) - Dai, Niann-Tzyy; Fu, Keng-Yen; Hsieh, Pai-Shan; Hung, Yu-Min; Fang, Yun-Lung; Huang, Nien-Chi; Lu, Tzu-Wei; Dai, Lien-Guo; Chen, Shyi-Gen; Chen, Tim-Mo
Abstract : Abstract: Massive bleeding is the leading cause of battlefield-related deaths and the second leading cause of deaths in civilian trauma centers. One of the challenges of managing severe wounds is the need to promote hemostasis as quickly as possible, which can be achieved by using hemostatic dressings. In this study, we fabricated 2 kinds of gelatin/polycaprolactone composites with 2 ratios of gelatin/polycaprolactone, 1:1 and 2:1 (GP11 and GP21, respectively). Scanning electron microscopy revealed that the GP11 composite exhibited rougher and more porous structure than the GP21 composite did. Furthermore, both composites showed similar biocompatibility as that of tissue culture polystyrene. Moreover, both GP composites tended to show a gradual decrease in contact angle to zero within 40 minutes. The in vitro blood plasma coagulation assay revealed that the prothrombin time was significantly longer for the GP composites than it was for the Quikclot composite, whereas the activated partial thromboplastin time of the GP11 composite was significantly shorter than that of the gauze. Furthermore, the GP11 had the largest platelet adsorption of all the composites. The in vivo coagulation test showed an obvious shortening of the bleeding time with the Quikclot and GP21 compared with gauze sample. In conclusion, the GP composites showed superior biocompatibility and hemostasis to the gauze and comparable effects with the Qickclot composite. Therefore, the GP composites have the potential for development as biodegradable surgical hemostatic agents.